The diagnostic challenges and two-step surgical approach to an infected dentigerous cyst resembling a unicystic ameloblastoma: A case report - Suryabharata, Cokorda Gde; Rizqiawan, Andra; Mulyawan, Indra; Wati, Sisca Meida; Rahman, Mohammad Zeshaan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: A dentigerous cyst is the second-most frequently observed odontogenic cyst, and an ameloblastoma is one of the most frequently observed odontogenic tumors. Both are mostly associated with an impacted mandibular third molar and have similar characteristics. Diagnostic difficulties often result in misdiagnosis and remain a challenge to overcome. Comprehensive clinical, radiographic, and histopathological views are essential to correctly diagnose the problem and formulate the most suitable treatment plan. Purpose: This case report aims to present a thorough approach to the diagnostic and surgical procedures involved in treating a dentigerous cyst that resembles an ameloblastoma by using marsupialization followed by enucleation. Case: This article presents the case report of a 27-year-old male patient with an infected dentigerous cyst resembling a unicystic ameloblastoma associated with a totally impacted lower mandibular left third molar. The patient had a history of swelling, pain, and pus drainage in the retromolar area. Symptoms subsided after antibiotic and analgesic prescriptions, but the lesion remained and was slowly progressing. The diagnostic approach began with a fine-needle aspiration biopsy, and the result confirmed a benign cystic lesion that was suspected to be an odontogenic tumor. Then an incisional biopsy was conducted under local anesthesia, diagnosing an infected dentigerous cyst. Case Management: Marsupialization and decompression using an obturator was preferred, followed by enucleation. Nine months later, a radiographic examination revealed satisfactory bone regeneration without recurrence. Conclusion: An incisional biopsy plays a vital role in establishing a definitive diagnosis. Marsupialization followed by enucleation offers an excellent combination of treatments achieving complete cyst removal, anatomical structure preservation, and bone regeneration with minimal complications.